Evolution and Refinement with Endogenous Mistake Probabilities - Eric van Damme; Jörgen W. Weibull (The Research Institute of Industrial Economics (IUI), 1999)
Bergin and Lipman (1996) show that the refinement effect from the random mutations in the adaptive population dynamics in Kandori, Mailath and rob (1993) and Young (1993) is due to restrictions on how these mutation rates vary across population states. We here model mutation rates as endogenously determined mistake probabilities, by assuming that players with some effort can control the probability of implementing the intended strategy. This is shown to corroborate the results in Kandori-Mailath-Rob (1993) and, under certain regularity conditions, those in Young (1993). The approach also yields a new refinement of the Nash equilibrium concept that is logically independent of Selten's (1975) perfection concept and Myerson's (1978) properness concept.
Keywords: C70; C72; 330; Game theory; Evolutionary game theory; refinement; Spieltheorie; Nash-Gleichgewicht; Theorie